A mobile phone app to support young people in making shared decisions in therapy (Power Up): study protocol - Chapman, Louise; Edbrooke-Childs, Julian; Martin, Kate; Webber, Helen; Craven, Michael P.; Hollis, Chris; Deighton, Jessica; Law, Roslyn; Fonagy, Peter; Wolpert, Miranda (JMIR Publications, 2017)
Background: Evidence suggests that young people want to be active participants in their care and involved in decisions about their treatment. However, there is a lack of digital shared decision-making tools available to support young people in child and adolescent mental health services (CAMHS). Objective: The primary aim of this paper is to present the protocol of a feasibility trial for Power Up, a mobile phone app to empower young people in CAMHS to make their voices heard and participate in decisions around their care. Methods: In the development phase, 30 young people, parents, and clinicians will take part in interviews and focus groups to elicit opinions on an early version of the app. In the feasibility testing phase, 60 young people from across 7 to 10 London CAMHS sites will take part in a trial looking at the feasibility and acceptability of measuring the impact of Power Up on shared decision making. Results: Data collection for the development phase ended in December 2016. Data collection for the feasibility testing phase will end in December 2017. Conclusions: Findings will inform the planning of a cluster controlled trial and contribute to the development and implementation of a shared decision-making app to be integrated into CAMHS.